Coexistence and Culture: Understanding Human Diversity and Tolerance in Human-Elephant Interactions - Thekaekara, Tarsh; Bhagwat, Shonil A.; Thornton, Thomas F. (Frontiers in Conservation Science, 2021)
There is a growing recognition of the importance of conservation beyond protected areas, in spaces of human-wildlife coexistence. Negative human-wildlife interactions are a key challenge, but a better understanding of the forms of tolerance and mutual accommodation would be useful for coadaptation toward coexistence. To date, however, studies of human-wildlife often have been limited by a largely quantified positivist epistemology, which elides the diverse cultural and ecological contexts which enable tolerance and coexistence between humans and wildlife to develop and adhere. In Gudalur, a plantation landscape in South India, about 150 elephants share space with a quarter of a million people. Using a quantified survey coupled with ethnographic fieldwork, we aim to better understand human diversity and tolerance of elephants that allows for coexistence. We find a marked difference between communities, with ethnicity being a better predictor of tolerance than the more tangible socio-economic or geographic variables such as income, education, land holding or cropping patterns. Using qualitative data, we identify three socio-cultural variables that are relevant to tolerance–a shared history of living with elephants, mode of subsistence and type of agricultural crops, and most importantly, ontology or the fundamental understanding of “what is an elephant?” Hunter-gatherer conceptualisations of elephants as “other-than-human persons” prove to be the ontological stance best suited to coexistence, as it allows for elephant individuality and interpersonal negotiations of shared space, which is limited in other world-views, including the worshiping of elephants as Ganesha, the elephant headed deity in the Hindu Pantheon. Having identified some important differences among ethnic communities in human-elephant interactions, we consider the implications of the research for improving the management and practice of human-wildlife coexistence not only in the Nilgiri region but within the broader context of conservation and development.